2010
DOI: 10.3146/ps09-001.1
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the Core Collection of Peanut Germplasm to Sclerotinia Blight and Pepper Spot1

Abstract: In 2001, entries from the peanut core collection, a subset of the USDA peanut germplasm collection, were planted in non-replicated plots in a field with a history of Sclerotinia blight caused by Sclerotinia minor. Variability existed among entries for reaction to Sclerotinia blight. Of the 744 entries evaluated, 11% had no disease, nearly 30% had ,10% disease incidence, and only 21% had 50% disease incidence or more. Most of the resistant entries had an upright growth habit and were in early and mid-maturity g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
(42 reference statements)
1
33
1
1
Order By: Relevance
“…resistance because other characteristics such as open canopy structure can create microclimates unfavorable for disease (Blad et al, 1978;Dow et al, 1988;Bailey and Brune, 1997). For example, the cultivar Southwest Runner (Damicone et al, 2010) and several mini-core accessions including CC038, CC068, and CC787 (Bennett et al, 2018) exhibit resistance to Sclerotinia minor in the field but are susceptible when inoculated in the laboratory. While severe outbreaks of A. rolfsii are rare in current peanut production areas of Oklahoma, an inoculated field study of the U.S. mini-core that included three cultivars used here indicated that the A. rolfsii assays may correlate with field results.…”
Section: Audpcmentioning
confidence: 99%
“…resistance because other characteristics such as open canopy structure can create microclimates unfavorable for disease (Blad et al, 1978;Dow et al, 1988;Bailey and Brune, 1997). For example, the cultivar Southwest Runner (Damicone et al, 2010) and several mini-core accessions including CC038, CC068, and CC787 (Bennett et al, 2018) exhibit resistance to Sclerotinia minor in the field but are susceptible when inoculated in the laboratory. While severe outbreaks of A. rolfsii are rare in current peanut production areas of Oklahoma, an inoculated field study of the U.S. mini-core that included three cultivars used here indicated that the A. rolfsii assays may correlate with field results.…”
Section: Audpcmentioning
confidence: 99%
“…Previously, the marker used in this study was shown to be significantly associated with resistance to Sclerotinia blight in peanut cultivars and PIs that had been thoroughly evaluated in field trials (Chenault et al, 2009). The marker has been used previously to screen numerous germplasm collections Chamberlin, 2014;Chamberlin and Puppala, 2018) and the results obtained have been shown to closely agree with phenotypic reaction to S. minor in field trials (Chenault et al, 2009;Chamberlin et al, 2010;Damicone et al, 2010;Bennett et al, 2018). The results of the current study are similar to those reported when the marker was used to screen other collections, with the marker for resistance being prominent in the fastigiata, vulgaris, and hirsuta botanical types.…”
Section: Resultsmentioning
confidence: 79%
“…Lariat is the result of a cross between the cultivar Red River Runner and US germplasm collection PI 274193, an accession identified by Damicone et al (2010) as having a prostrate growth habit and excellent resistance to Sclerotinia blight, web blotch (caused by Phoma arachidicola Marasas et al), and pepper spot [caused by Leptosphaerulina crassiasca (Sechet) C.R. Jackson & D.K.…”
Section: Methodsmentioning
confidence: 99%
“…Lariat is the result of a cross between the cultivar Red River Runner and US germplasm collection PI 274193, an accession identiied by Damicone et al (2010) (Chenault et al, 2009) and tested for high-oleic oil quality in 2006 to 2007 . F 3 seed positive for both traits was space planted in 2008 in breeding nursery plots at the Oklahoma Agricultural Experiment Station (Caddo Research Station) at Fort Cobb, OK.…”
Section: Crossing and Early Stage Development And Line Selectionmentioning
confidence: 99%